Evaluation of an O2-Substituted (1–3)-β-D-Glucan, Produced by Pediococcus parvulus 2.6, in ex vivo Models of Crohn’s Disease - Notararigo, Sara; Varela, Encarnación; Otal, Anna; Cristobo, Iván; Antolín, María; Guarner, Francisco; Prieto, Alicia; López, Paloma (Frontiers in Microbiology, 2021)
1,3-β-glucans are extracellular polysaccharides (EPS) synthesized by microorganisms and plants, with therapeutic potential. Among them, the 2-O-substituted-(1-3)-β-D-glucan, synthesized by some lactic acid bacteria, has a prebiotic effect on probiotic strains, an immunomodulatory effect on monocyte-derived macrophages, and potentiates the ability of the producer strain to adhere to Caco-2 cells differentiated to enterocytes. In this work the2-O-substituted-(1-3)-β-D-glucan polymers produced by GTF glycoyltransferase in the natural host Pediococcus parvulus 2.6 and in the recombinant strain L. lactis NZ9000[pNGTF] were tested. Their immunomodulatory activity was investigated in an ex-vivo model using human biopsies from patients affected by Crohn’s disease. Both EPS had an anti-inflammatory effect including, a reduction of IL-8 both at the level of its gene expression and its secreted levels. The overall data indicate that the 2-O-substituted-(1-3)-β-D-glucan have a potential role in ameliorating inflammation via the gut immune system cell modulation.